Madhav Gadgil (1942–2026): A pioneering Indian ecologist’s legacy of biodiversity conservation and human coexistence - Krushnamegh Kunte; Utkarsh Ghate; K. A. Subramanian (Proceedings of the National Academy of Sciences, 2026)
Madhav Gadgil was an evolutionary ecologist and champion of governmental and intergovernmental policies for biodiversity conservation, human coexistence with nature, and indigenous rights to land, natural resources, and self-governance. He made foundational contributions to the development of biodiversity sciences, human ecology, people’s traditional knowledge—and inherent rights to that knowledge as documented through biodiversity registers. Gadgil advocated a coherent policy integrating human welfare and biodiversity conservation in India. He will be remembered as an academic giant and an unmatched thinker, policy advocate, institution-builder, and humanitarian.